2018
DOI: 10.1016/j.neulet.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota impact sepsis associated encephalopathy via the vagus nerve

Abstract: FMT can change intestinal microbiota in sepsis patients, and vagus nerve is a key mediator between intestinal microbiota and SAE. These findings suggest that FMT and vagus nerve are potential therapy targets for treating SAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 32 publications
1
40
0
2
Order By: Relevance
“…Patients with sepsis that is directly influenced by gastrointestinal infection or antibiotic administration [28] may develop disturbances of the gut microbiota. Animal experiments have found that faecal bacteria transplantation can change the gut microbiota of septic mice, suggesting that faecal bacteria transplantation and vagal nerve block are potential therapeutic targets in SAE [29]. The effects of gut microbiota disturbance and the GBA on SAE development deserve further study, especially with respect to upstream and downstream initiation mechanisms, which may provide more ideas to explore the pathogenesis and early diagnosis of SAE.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with sepsis that is directly influenced by gastrointestinal infection or antibiotic administration [28] may develop disturbances of the gut microbiota. Animal experiments have found that faecal bacteria transplantation can change the gut microbiota of septic mice, suggesting that faecal bacteria transplantation and vagal nerve block are potential therapeutic targets in SAE [29]. The effects of gut microbiota disturbance and the GBA on SAE development deserve further study, especially with respect to upstream and downstream initiation mechanisms, which may provide more ideas to explore the pathogenesis and early diagnosis of SAE.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a mouse model of Streptococcus pneumoniae sepsis, pre-treatment with oral antibiotics prior to sepsis onset was associated with lower levels of lung TNF-α, a pro-inflammatory cytokine [25], whereas others have shown the opposite effect of gut microbiome depletion on TNF-α [21,22,[37][38][39]. Despite differences in specific cytokine expression between studies, the overall effect of alteration of normal gut microbiome structure prior to sepsis onset appears to be a more robust inflammatory response to sepsis [21,22,25,[37][38][39][40][41].…”
Section: Altered Immune Responsementioning
confidence: 99%
“…The pathogenesis of SAE remains poorly understood. 15 Increasing evidence showed that neuronal dysfunction TIAN ET AL.…”
Section: Lps-induced Sae and Cognitive Dysfunctionmentioning
confidence: 99%